Conical voltage sensor for measuring very fast transient overvoltage up to 3 MV in ultra‐high‐voltage class gas‐insulated switchgear. Issue 3 (1st May 2018) - Zhang, Lu; Mao, Chen; Pu, Lu; Wu, Jingfeng; Wang, Sen; Ding, Bin; Sun, Lei; Zhang, Qiaogen
Abstract : Very fast transient overvoltage (VFTO) engenders great threat to gas‐insulated switchgear (GIS) in ultra‐high‐voltage (UHV) power system. A novel conical voltage sensor was developed based on combination of the conical voltage divider and coaxial integral device to measure VFTO in UHV GIS. The results indicate that the conical structure of the voltage sensor can make the wave impedance translate smoothly from the high‐voltage arm to the coaxial cable, which significantly reduces refraction and reflection of VFTO. The optimum value of the integral capacitance is between 100 and 200 pF, which is determined by the integral resistance, capacitance of the sensor, and the length of the transmission line. To avoid refraction and reflection of VFTO in the process of transmission, the length of the transmission cable should not exceed 20 cm. Calibration results show that the response time of the conical voltage sensor is <4.8 ns, the voltage attenuation ratio of the sensor can reach up to 43, 402 and the frequency band is between 7.8 Hz and 73 MHz. The conical voltage sensor was tested on a steep impulse voltage equipment, and the result showed the sensor could measure VFTO up to 3 MV.